Mahabbah Kepada Rasulullah Perspektif Hadis (Analisis Hadis dalam Kitab Nurul Mubin fi Mahabbati Sayyidil Mursalin Karya K.H Hasyim Asy’ari) - Muhammad Yazid Arrizqi (UIN Sunan Gunung Djati Bandung, 2023)
Mahabbah or love for the Prophet is a manifestation of the perfection of a Muslim's faith in Allah SWT. and His Messenger. This study aims to discuss about mahabbah to Rasulullah from the perspective of hadith in the book of Nurul Mubin fi Mahabbati Sayyidil Mursalin by K.H Hasyim Asy'ari. This research is a qualitative type through literature study with the syarah hadith method. The results and discussion of this study include the biography of K.H Hasyim Asy'ari, the hadith about mahabbah to the Prophet in the book of Nurul Mubin fi Mahabbati Sayyidil Murslain and the concept of mahabbah to the Prophet from the perspective of hadith according to K.H Hasyim Asy'ari. This study concludes that according to K.H Hasyim Asy'ari, loving the Prophet is proof of love for Allah SWT. Then someone who loves the Messenger of Allah will always increase sholawat to him, and draw closer to Allah SWT. through the washing of the Messenger of Allah. This study recommends that every Muslim can increase their faith and love for Allah SWT. and the Messenger of Allah. as proof of faith.